Relationship between time and goal scoring of European soccer teams with different league ranking - Evangelos, B.; Gioldasis, A.; Ioannis, G.; Georgia, A. (Journal of Human Sport & Exercise, 2018)
The aim of the current study was to compare scored and conceded goals as well as the time period among teams of different league ranking. Researchers recorded the total games (n= 1446) of the top European leagues of Spain, Italy, Germany, and France for the period 2015-2016. The teams were divided into the ones which achieved their participation for European cups (L1), teams that remained to the category (L2), and teams which relegated to the lower category (L3). The researchers recorded the scored goals, the conceded goals, and the goal differences, per game, per half, and per 15min in total games for 2015-2016 season. The results showed that L1 teams were superior to L2 and L3 in overall goal scoring characteristics in both halves. The superior 15min periods were also explored. In addition, L2 teams performed higher than L3 teams in most of the variables. In conclusion, the difference between L1 with L2 and L3 teams is based in goal scoring during the whole game, in contrast with the difference between L2 and L3 teams that relies on stronger defense. On the other hand, L3 teams did not perform higher in any goal scoring pattern than the other two groups. It is obvious, that performance difference is achieved by the first half which is difficult to change during the second half. Thus, coaches have to emphasize achieving high performance in the first half of the game. Furthermore, they must use their substitutions so as to avoid poor performance periods and heighten the offensive and defensive play of their teams.